"Dig Deep and Reach Wide": The Changing Politics of the Chinese Communist Party's Consultative Information System. (30th March 2023) - Zhao, Taotao
Abstract: Since the early 2010s, a low-profile "dig deep and reach wide" campaign led by local Chinese Communist Party (CCP) committees has unprecedently institutionalized and embedded academic opinions into the regimes' decision-making processes. This research aims to deepen the existing understanding of the intricate relationship between players in the CCP's decision-making process by analysing the Party's deliberation on scholarly opinions through an academic lens. It argues that the local Party committees' incentives to incorporate academic opinions into their information channels are not only a reaction to the central CCP's increasing need to "reach wide" for high-quality and critical policy proposals but are also a move to seek political endorsement from the central authorities. This process has transformed government–academic relations in China from a patron-client model to one of increasing interdependence in which Chinese academia has become increasingly attuned to the thinking and needs of the CCP.